Anatomical variations of Deschampsia antarctica É. Desv.plants from distant Antarctic regions, in vitro culture, and in relations to Deschampsia caespitosa (L.) P. Beauv. - Nataliia Nuzhyna; Ivan Parnikoza; Oksana Poronnik; Iryna Kozeretska; Viktor Kunakh (Polish Polar Research, 2019)
This paper presents a comparative study on the anatomy of the Antarctic hairgrass (Deschampsia antarctica É. Desv.) from natural populations of two distant maritime Antarctic regions: the Argentine Islands (Antarctic Peninsula region) and the Point Thomas oasis (King George Island, South Shetland Islands). Comparison of D. antarctica plants from natural populations of Argentine Islands region and plants originated from seeds of these populations cultivated in vitro also was made. Additionally anatomical features of Deschampsia antarctica were compared with ones for D. caespitosa. The results of our study do not provide enough evidence to assert more pronounced xerophytic anatomical features in D. antarctica plants from more harsh conditions of Argentine Islands region. Such features (both qualitative and quantitative) of D. antarctica mainly depend on local conditions, and not on the latitudinal or climatic gradient. In both regions it is possible to find individuals that represent different ecotypes which are adopted to open arid or more humid habitats. It has been shown that Antarctic hairgrass plants germinated from seeds and cultivated in vitro retain the qualitative anatomy features that are typical to plants from the initial natural populations. This is especially noticeable in the case of plants from Berthelot Island (BE1 study plots), which might indicate a genetic fixation and a manifested differentiation similar to DNA haplotypes or chromosomal forms. However, quantitative characteristics, in particular the epidermis parameters, are subject to changes due to the transfer to more favourable conditions. Also qualitative and quantitative difference of D. antarctica in contrast with D. caespitosa have been described. These differences could be useful for identifying these two species. Additionally the quantitative differences (such as the area of the epidermal cells and the number and size of stomata on the adaxial surface) of Alaskan D. caespitosa grown from seeds were detected in contrast to the naturally grown plants of the same species from Ushuaia.